Comparison of Growth of Chlorella vulgaris in Flat-Plate Photobioreactor Using Batch, Fed-Batch, and Repeated Fed-Batch Techniques with Various Concentrations of Walne Medium - Trinh, Khanh Son (Journal of Technical Education Science, 2023)
Chlorella vulgaris was autotrophically grown in a Flat-Plate Photobioreactor (FPPB) using batch (BC), fed-batch (FB), and repeated fed-batch (RPF) cultivations. BC stage was done in the 20 L of working volume. During FB stages, 20 L of fresh medium was added to reach the final volume of 60 L. In the RPF stages, 20 L of broth was harvested, and then a similar volume of fresh medium was added to keep the working volume. This study aimed to evaluate the effect of Walne media (with various concentrations of composition) and cultural techniques on algal growth. Three different concentrations of Walne medium (original [coded as ´1], double [coded as ´2], and triple [coded as ´3] in concentrations of the original medium) was used for cultivations. Not only culture techniques but also various media affected biomass and chlorophyll productivity. RPF (with ´2 cultivation) gave the highest biomass productivity. However, RPF (with ´1 cultivation) gave the highest chlorophyll productivity. So, this study showed much fundamental information for the industrial production of Chlorella vulgaris biomass using flat-plate photobioreactors.